2020
DOI: 10.1016/j.triboint.2020.106252
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the role of surface textures in improving the performance of boundary additives, part II: Numerical simulations

Abstract: This is a repository copy of Understanding the role of surface textures in improving the performance of boundary additives, part II: Numerical simulations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…It can basically be considered that the state that the relaxation-process time is 0 min as shown in figure 20 Figure 20 demonstrates that the average friction coefficient with the relaxation-process time of 0 min is lower than that with the relaxation-process time of 20 min. While the fluctuation of the friction The investigations [23,47] on the lubricant infiltration effects have revealed that the influence of the interaction (e.g., contact pressure and relative velocity) between the upper and lower samples of the friction pairs on the lubricant infiltration is important. A direct exploration of the effect of the velocity and contact pressure on the lubricant infiltration capacity is challenging, since the flow behaviors (e.g., lubricant spatter, lubricant separation and lubricant convergence) of the lubricant during the friction processes demand a high measurement effort.…”
Section: Effect Of the Lubricant Infiltration Capacity On The Tribolo...mentioning
confidence: 99%
“…It can basically be considered that the state that the relaxation-process time is 0 min as shown in figure 20 Figure 20 demonstrates that the average friction coefficient with the relaxation-process time of 0 min is lower than that with the relaxation-process time of 20 min. While the fluctuation of the friction The investigations [23,47] on the lubricant infiltration effects have revealed that the influence of the interaction (e.g., contact pressure and relative velocity) between the upper and lower samples of the friction pairs on the lubricant infiltration is important. A direct exploration of the effect of the velocity and contact pressure on the lubricant infiltration capacity is challenging, since the flow behaviors (e.g., lubricant spatter, lubricant separation and lubricant convergence) of the lubricant during the friction processes demand a high measurement effort.…”
Section: Effect Of the Lubricant Infiltration Capacity On The Tribolo...mentioning
confidence: 99%
“…Due to MoS2 sheet formation in the tribological contact area, the reduction of the coefficient of friction values occurs [10][11][12][13][14]. MoDTC decomposition and MoS2 tribofilm formation can be influenced by many factors like oil formulation chemistry [14,15], tribological contact conditions such as surface roughness [16], texturing [17,18], temperature [12] and interacting surface materials [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have indirectly given evidence about the effect of roughness on tribofilm growth or vice versa. Recently, a study 48,49 suggested that surface textures that result in greater pressures, thicker lubricant films and greater contact area hold promise for optimal performance under tribochemically active conditions. Azam et al 27 performed a simulation study and suggested that the growth of tribofilm leads to increased lubricant entrapment.…”
Section: Introductionmentioning
confidence: 99%